THE ROLE OF SYMBOLS IN SHAPING CULTURAL IDENTITY (World Bulletin of Education and Learning, 2025)
This article examines bird symbolism as a culturally embedded system of meaning across different civilizations. It explores how birds function as symbols of spirituality, the soul, wisdom, power, and transcendence in religious, literary, and philosophical traditions. Special attention is given to Eastern and Western perspectives, highlighting how cultural context shapes symbolic interpretation. The study demonstrates that bird symbolism reflects collective worldviews and evolving human conceptions of the sacred and the existential.
Keywords: Symbolism, cultural identity, spirituality, religious, literary, philosophical traditions, Eastern and Western perspectives.